Factors Influencing Interest in Buying the Shopee Marketplace During the Covid-19 Pandemic - Yustika, Rita; Putra, Awang Darmawan; Pasaribu, Popy Novita (Jurnal Manajemen, 2023)
This study analyzes consumer buying behavior during the Covid-19 pandemic which had an impact on people's lives, especially economic conditions. To avoid the spread of the coronavirus, the government implements provisions for completing community life activities, on the other hand, people who are faced with risk factors avoid direct transactions. The impact felt by the community is the limitation of direct spending to meet daily needs, so people switch from shopping directly to shopping in the marketplace. This research examines the impact of the crisis during the pandemic on the purchasing behavior of marketplace Shopee consumers. This paper is based on the results of a quantitative analysis involving 100 respondents in Bogor and its surroundings. This study was conducted in November 2022. Partial and simultaneous data analysis showed that the independent variable perceived usefulness, perceived severity of the covid pandemic, perceived risk management, and perceived trust had a significant influence on the variable purchase intention (Y) at the Shopee marketplace during the pandemic. at Bogor. The results of the summary model test obtained a coefficient of determination of 0.463 which implies that the model can explain the intention to buy the Shopee market place 46.3%. Partial results show that perceived trust and perceived usefulness significantly influence shopping intentions using the Shopee marketplace in Bogor